POTENCIAL OF THE INTERNET AS A MARKETING MEDIUM - Madlenak, Radovan (Doprava a spoje, 2005)
Advertising and commercial activities on the Internet are the recent trends of the last few years. The Internet is regarded as effective way of communicating with the market, and ideal instrument for looking for potential customers. This article deals with same aspects of using Internet as a marketing medium, which becomes suitable for creation a successful relation between firms and consumers.